What support is needed prior to the designation as baby-friendly hospital? - Eman F. Badran; Reema Safadi; Raeda Al Qutob; Dua' Al-Maharma; Aseel A. Qutaishat; Deema F. Masarweh; Yazeed A. Bani-Hamad; Ahmad B. Khamees; Asma R. Shabsough; Basheer Khamees (Elsevier, 2022)
Introduction: Breastfeeding rates remain low in Jordan. Exploring facilitators and barriers contributing to women's difficulties in juggling exclusive breastfeeding (EBF ≤ 6months) and work to achieve positive outcomes, is critical. Aim: To assess EBF rate and challenges faced by mothers after returning to work at a hospital setting prior to its designation as a Baby Friendly Hospital. Methods: face to face cross-sectional study using validated questioner was conducted over a one-month period on all 75 working mothers at our institute who had a new baby aged 6-48 months before the study date. Results: The EBF initiating rate was 56%. The perceived identified barriers include a lack of flexibility in the work schedule for breast feeding/milk expression, a lack of pumping space, dissatisfaction with maternity leave, and concerns about support from supervisors and co-workers' employers. The adherence to EBF among mothers who had co-worker support, self-confidence of EBF, and environmental support at the workplace differed significantly from those who did not have these conditions (p < 0.05). Conclusion: Despite putting confidence in EBF and family/partner support, the mother's return to work was a significant impediment to EBF continuation.Mothers' adherence to exclusively nursing their infants increased if they had environmental support at work and co-worker employee support.